The The Influence of HDI, Minimum Wage and TPAK on Poverty With ZIS as Moderation in East Java 2018-2023: The Influence of HDI, Minimum Wage and TPAK on Poverty With ZIS as Moderation in East Java - Aris Yuliana, Aris Yuliana; Mohammad Sholeh; Syifa Rohmah (Journal Of Islamic Economics And Finance, 2025)
This study aims to analyze the effect of Human Development Index (HDI), Minimum Wage, and Labor Force Participation Rate on Poverty with ZIS as a Moderating Variable in East Java from 2018 to 2023. The background of this study is based on the high number of poor people in East Java in 2023, the uneven poverty reduction targets in East Java from 2018 to 2023, and the differences in the results of previous studies. The method used was a quantitative panel data approach. The sampling technique used purposive sampling, which obtained 30 districts and cities in East Java as samples. The data analysis technique used Moderated Regression Analysis (MRA). The results showed that HDI and labor force participation rate had a negative and significant effect on poverty, while minimum wage had a positive and insignificant effect on poverty. In addition, the distribution of ZIS funds was found to moderate the effect of the minimum wage and HDI on poverty, but it was not able to moderate the effect of labor force participation rate on poverty. These findings confirm that strengthening the distribution of ZIS can be a concrete implementation of maqashid syariah in realizing social welfare and poverty reduction.